Non-Standard Employment in Uzbekistan in Times of Digital Economy Development - E. F. Turaeva (Вестник Российского экономического университета имени Г. В. Плеханова)
In conditions of digital economy development non-standard employment becomes more and more important on labour market of Uzbekistan. In spite of its potential advantages, such as flexibility and feasibility of entrepreneurship non-standard employment brings its challenges, for example absence of social welfare and stable income. The author of the article analyzed the current standing of non-standard employment in Uzbekistan, showed key trends and challenges and also provided recommendations for improvement of the situation. The research findings highlighted the importance of developing adequate measures aimed at ensuring just working conditions and social welfare for all workers irrespective of their employment.